Adherence to Hemodialysis and Associated Factors among End Stage Renal Disease Patients at Selected Nephrology Units in Rwanda: A Descriptive Cross-Sectional Study - Marie Claire Mukakarangwa; Geldine Chironda; Busisiwe Bhengu; Godfrey Katende (Nursing Research and Practice)
Introduction. Worldwide, End Stage Renal Disease (ESRD) has become a public health concern increasing the number of patients maintained on hemodialysis prior to renal transplantation. Nonadherence to hemodialysis continues to impact on the care of ESRD patients, causing high increase in morbidity and mortality. Purpose of the Study. The purpose of this study was to determine the level of adherence to hemodialysis and the associated factors among End Stage Renal Disease (ESRD) patients in selected nephrology units in Rwanda. Methods. This was a descriptive cross-sectional design involving 41 participants. Participants were recruited using a purposive sampling technique. Demographic and adherence to hemodialysis data were collected with the use of structured interview schedules. Descriptive statistics were used to describe the demographic variables and the level of adherence to hemodialysis. Inferential statistics of chi-square was used to establish factors associated with adherence to hemodialysis. Results. Twenty-one (51%) of ESRD participants adhered highly (scores < 80%) to HD. Seventeen (42%) adhered moderately (70–79%) to HD while three (7%) had low level of adherence to HD (below 70%). The factors associated with adherence to hemodialysis were age (mean = 27; 95% CI 26.76–29, 17; p = 038) and religion (95% CI 26.29–60.12, p = 003). Frequencies of education of health care workers about the importance of not missing dialysis (95% CI 26.71–42.56, p = .000), perceived relative importance of hemodialysis (95% CI 20.44–27.76, p = .020), and experiencing difficulties during the procedure (95% CI 20.80–28.36, p = .004) were significantly associated with adherence to hemodialysis. Conclusion. Adherence to hemodialysis is still a public health concern in Rwanda. Health care providers and particularly nurses should continue to advocate for adherence to HD for better health outcomes. Further research is needed to identify the barriers to HD in Rwanda.